ANTESEDEN DAN KONSEKUENSI KEPUASAN PELANGGAN DALAM KONTEKS WORD-OF-MOUTH - Sukaris sukaris (Jurnal Manajerial, 2019)
The purpose of this study is to analyze the antecedents and consequences of customer satisfaction in context of Word-of-Mouth. Data was collected through quizzes from "students of the Faculty of Economics Business University of Muhammadiyah Gresik (FEB-UMG). The results of the study show that service quality has an effect on customer value, quality service and customer value have an effect on customer satisfaction and customer satisfaction has an effect on positive words of mouth of FEB-UMG students. Further research on the topic of customer value, many factors can be used as response variables other than service quality including company reputation, benefits of service use, community effects and marketing mix. While the trust variable in higher education can be included as a response variable to customer satisfaction